Enhanced AAβ cryptosystem: the design - Asbullah, Muhammad Asyraf; Kamel Ariffin, Muhammad Rezal; Mahad, Zahari (Institute for Mathematical Research, Universiti Putra Malaysia, 2018)
This paper presents an enhancement of the AAβ cryptosystem. Our approach is to adjust the key generation algorithm and incorporate the Rabin-p decryption techniques upon the AAβ decryption procedure. As a result, in comparison to any versions of AAβ cryptosystem prior to this work, the enhanced AAβ cryptosystem is superior in term of smaller key sizes, and have computational advantageous in decryption procedure. Consequently, we show that breaking the AAβ cryptosystem is computationally reduce to solving the Rabin-p cryptosystem, and (partially) vice versa.